Is the Duration of Diabetes Diseases Positively Associated With Knowledge About Diabetic Complications? Knowledge of Diabetes Mellitus Complications and Associated Factors Among Type-2 Diabetic Patients in Public Hospitals of Addis Ababa, 2020 - Chekol, Getachew Zewdu; Mengistu, Daniel; Tadesse, Addisu Waleligne (Frontiers in Public Health, 2022)
Background: Although the importance of educational programs in the prevention and control of DM and its complication is well recognized, there are concerns about whether these programs are achieving the desired goal of increasing knowledge of DM and its complication in developing countries. Therefore, this study assessed knowledge of diabetes mellitus complications and associated factors among Type-2 diabetic patients in public hospitals of Addis Ababa. Method: Simple random sampling technique was used to select 422 participants. Data were entered to EpiData Version 4.6.0.1 and analyzed using SPSS Version 25 software. Multicollinearity and Model goodness-of-fit was checked. A multivariate logistic regression model at 95% CI was used to identify the predictors. Result: The overall knowledge of diabetes complications among diabetic patients in the Hospitals of Addis Ababa was 54.9%. In the fitted model, being a profession of governmental workers [AOR=3.12, 95% CI (1.33, 7.34)] and merchants [AOR=2.54, 95% CI (1.16, 5.56; DM duration 5 to 10 years [AOR=0.41, 95% CI (0.23, 0.73)] and ≥10 years [AOR=0.36, 95% CI (0.19, 0.69)]; family history of DM [AOR=1.68, 95% CI (1.03, 2.75)] and participating in diabetic counseling [AOR=2.41, 95% CI (1.50, 3.86)] were significantly associated with knowledge about DM complications. Conclusion and Recommendation: The overall knowledge of diabetes complications among diabetic patients in the Hospitals of Addis Ababa was 54.9%. It was determined by the duration of diabetes mellitus, current profession, family history, and participation in diabetes counseling. Hence, emphasize sustaining knowledge about diabetes complications for patients who are more than five years since diagnosis and attention are needed about knowledge diabetic farmers.